Inorganic polyphosphate is a potent activator of the mitochondrial permeability transition pore in cardiac myocytes - Seidlmayer, Lea K. (The Rockefeller University Press, 2012)
Mitochondrial dysfunction caused by excessive Ca(2+) accumulation is a major contributor to cardiac cell and tissue damage during myocardial infarction and ischemia–reperfusion injury (IRI). At the molecular level, mitochondrial dysfunction is induced by Ca(2+)-dependent opening of the mitochondrial permeability transition pore (mPTP) in the inner mitochondrial membrane, which leads to the dissipation of mitochondrial membrane potential (ΔΨ(m)), disruption of adenosine triphosphate production, and ultimately cell death. Although the role of Ca(2+) for induction of mPTP opening is established, the exact molecular mechanism of this process is not understood. The aim of the present study was to test the hypothesis that the adverse effect of mitochondrial Ca(2+) accumulation is mediated by its interaction with inorganic polyphosphate (polyP), a polymer of orthophosphates linked by phosphoanhydride bonds. We found that cardiac mitochondria contained significant amounts (280 ± 60 pmol/mg of protein) of short-chain polyP with an average length of 25 orthophosphates. To test the role of polyP for mPTP activity, we investigated kinetics of Ca(2+) uptake and release, ΔΨ(m) and Ca(2+)-induced mPTP opening in polyP-depleted mitochondria. polyP depletion was achieved by mitochondria-targeted expression of a polyP-hydrolyzing enzyme. Depletion of polyP in mitochondria of rabbit ventricular myocytes led to significant inhibition of mPTP opening without affecting mitochondrial Ca(2+) concentration by itself. This effect was observed when mitochondrial Ca(2+) uptake was stimulated by increasing cytosolic [Ca(2+)] in permeabilized myocytes mimicking mitochondrial Ca(2+) overload observed during IRI. Our findings suggest that inorganic polyP is a previously unrecognized major activator of mPTP. We propose that the adverse effect of polyphosphate might be caused by its ability to form stable complexes with Ca(2+) and directly contribute to inner mitochondrial membrane permeabilization.